Diversity and abundance of beetle at Kuala Kelapor, National Park, Malaysia - Musthafa, Muneeb M.; Rajandram, Davindran; Abdullah, Fauziah (Universiti Kebangsaan Malaysia Press, 2019)
National Park is one of the oldest rainforests found in South-east Asia andit hasa very complex ecosystem. The objective of this study was to preparean inventory on beetle abundance and diversity at Kuala Kelapor National Park, Malaysia. Beetles were sample during pitfall traps, Malaise traps and light traps at five different trails in April 2015. This study successfully recorded709 individuals of beetles from 93 different species belonging to 26 different families. The most abundant species was Coccotrypes sp. 1, followed by Coccotrypes sp. 2 and Aetheomorpha sp. 1. The abundant beetle families were Curculionidae, Chrysomelidae and Scarabaeidae. Light traps and pitfall traps showed almost identical number of beetles collected, while Malaise traps recorded of107 individuals. Higher number of beetles were collected from Trail 3, followed by Trail 1 and base camp. The Shannon diversity index, Simpson diversity index and Fisher alpha diversity showed higher diversity values, which suggests that National Park accommodates a high diversity of beetles. Abundance is measured using Margalef index and Menhinick indices, showed values of 13.88 and 3.47, respectively. This information could be used as an initial step to analyze the potential use of beetles as a bioindicator group in Malaysia and climate change studies. © 2019, Universiti Kebangsaan Malaysia Press. All rights reserved.